Enhanced growth of chili (Capsicum annuum L.) by silicon nutrient application in fertigation system - Suhaizan Lob,; Nur Syakirah Sa’ad,; Nurul Faziha Ibrahim,; Norhidayah Che Soh,; Ramisah Mohd Shah,; Muhammad Safwan Hafiz Zaudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Silicon (Si) is one of the most abundant elements naturally available in the soil. This element performs an essential function in improving plant growth. This present study was carried out to evaluate the impact of Si nutrient application on the growth performance of chili (Capsicum annuum L.). Chili plant grown using a fertigation system was subjected to manual application of a silicon nutrient solution in varying concentrations (0 ppm, 108 ppm, 180 ppm, & 360 ppm) via root application. Each treatment was replicated five times, with five plants in each replicate, and all plants were grown in a shade house. The growth performance parameters measured were the number of leaves, stem diameter, plant height, plant biomass (dry weight), and Si accumulation in the stem, leave, and chili fruit. Results showed that Si nutrient application significantly affected the growth performances of chili plants. Application of T3 (360 ppm Si nutrient) was able to produce the highest stem diameter (8.92 mm), fresh weight (129.63 g), dry weight (67.23 g), as well as Si accumulation in stem (54 ppm), and chili fruit (24 ppm). On the other hand, applications with T2 (180 ppm Si nutrient) also demonstrated the highest plant height (20.98 cm), number of leave (27), and Si accumulation in leave (87 ppm). In conclusion, the application of silicon nutrients has the potential to enhance plant growth in numerous crops, making it a beneficial supplement to traditional agricultural practices.